Sludge palm oil as a renewable raw material for biodiesel production by two-step processes - Hayyan, Adeeb; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Mohd Hakimi, Noor Irma Nazashida; Mohd Siran, Yosri; Tahiruddin, Shawaluddin (Elsevier, 2010)
In this study, biodiesel was produced from sludge palm oil (SPO) using tolune-4-sulfonic monohydrate acid (PTSA) as an acid catalyst in different dosages in the presence of methanol to convert free fatty acid (FFA) to fatty acid methyl ester (FAME), followed by a transesterification process using an alkaline catalyst. In the first step, acid catalyzed esterification reduced the high FFA content of SPO to less than 2% with the different dosages of PTSA. The optimum conditions for pretreatment process by esterification were 0.75% (w/w) dosage of PTSA to SPO, 10:1 M ratio, 60 C temperature, 60 min reaction time and 400 rpm stirrer speed. The highest yield of biodiesel after transesterification and purification processes was 76.62% with 0.07% FFA and 96% ester content. The biodiesel produced was favorable as compared to EN 14214 and ASTM 6751 standard. This study shows a potential exploitation of SPO as a new feedstock for the production of biodiesel.